2023
DOI: 10.1177/00223433221146577
|View full text |Cite
|
Sign up to set email alerts
|

Protests and persuasion: Partisanships effect on evaluating nonviolent tactics in the United States

Abstract: How does the public respond to nonviolent resistance tactics? This survey experiment examines both approval and perceptions of legitimacy for five nonviolent tactics using a sample of American adults. We include two variations in our treatment – first examining responses to different protest tactics, then adding in the factor of co-partisanship, which we argue is a relevant identity in the US political context. In the non-partisan treatments, we find a stark dichotomy between our measures of approval and legit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Wasow (2020) found counties proximate to nonviolent Black protests 1960-1972 increased Democratic voting while counties proximate to protester-initiated violence shifted White voters toward Republicans. Other studies finding positive effects of protests that do not contrast nonviolent and violent protests include Biggs and Andrews (2015), Gillion and Soule (2018), Gillion (2013), Andrews, Beyerlein and Farnum (2016) and Shuman et al (2022) There is accumulating evidence that, while disruptive or violent protest may reduce approval of the protesters Kovacheff 2020, Simpson, Willer andFeinberg 2018), especially from those who are not core supporters (Croco, Cunningham andVincent 2023, Muñoz andAnduiza 2019), it often increases support for the policies the protesters support or for more moderate groups advocating similar issues (Simpson, Willer and Feinberg 2022). A survey of people living or working in South Central Los Angeles in 1992 found that most objected to the riot in principal but believed it had positive consequences (Murty, Roebuck and Armstrong 1994).…”
Section: News Media and The Percep�on Of Violence And Disrup�onmentioning
confidence: 99%
“…Wasow (2020) found counties proximate to nonviolent Black protests 1960-1972 increased Democratic voting while counties proximate to protester-initiated violence shifted White voters toward Republicans. Other studies finding positive effects of protests that do not contrast nonviolent and violent protests include Biggs and Andrews (2015), Gillion and Soule (2018), Gillion (2013), Andrews, Beyerlein and Farnum (2016) and Shuman et al (2022) There is accumulating evidence that, while disruptive or violent protest may reduce approval of the protesters Kovacheff 2020, Simpson, Willer andFeinberg 2018), especially from those who are not core supporters (Croco, Cunningham andVincent 2023, Muñoz andAnduiza 2019), it often increases support for the policies the protesters support or for more moderate groups advocating similar issues (Simpson, Willer and Feinberg 2022). A survey of people living or working in South Central Los Angeles in 1992 found that most objected to the riot in principal but believed it had positive consequences (Murty, Roebuck and Armstrong 1994).…”
Section: News Media and The Percep�on Of Violence And Disrup�onmentioning
confidence: 99%
“…Our contributions feature a wide range of methodological and empirical approaches, demonstrating the pluralistic approaches to these topics that have emerged in recent years. Among the contributions, we see the use of novel datasets (Dahlum, 2023; Kang, 2023; Nilsson & Svensson, 2023; Shay, 2023), qualitative process tracing (Clarke, 2023), observational data analysis (Cunningham, 2023; Dorff, Adcox & Konet, 2023; Turner, 2023), field surveys (Croco, Cunningham & Vincent, 2023; Grewal, Kilavuz & Kubinec, 2023) and mixed methodologies (Sombatpoonsiri, 2023). Methodological pluralism leads to more generalizable findings and greater engagement with a broader research and policy community.…”
Section: Introductionmentioning
confidence: 99%